2017
DOI: 10.1007/s10068-017-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Residue analysis of picoxystrobin in oriental melon using gas chromatography coupled with electron capture detection and mass spectrometric confirmation: application to dissipation kinetics and risk assessment

Abstract: This study was carried out to determine the residual amounts of picoxystrobin in oriental melon ( L.) grown under plastic house conditions at two different sites. Samples collected over 10 days were extracted using acetonitrile and salting out (using solid sodium chloride) and purified using Florisil SPE cartridges. The analyte was determined using GC-ECD and field-incurred residues were verified using GC-MS. The calibration curve was linear over the range 0.02-2.0 mg/L with a = 0.9998. The LOD and LOQ were 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…reported the half‐lives of picoxystrobin were 1.5–8.6 days in soil and 2.1–2.8 days in peanut seedlings 14 . The dissipation half‐lives of picoxystrobin in oriental melon were 3.4–3.7 days reported by Kabir et al 15 . You et al .…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…reported the half‐lives of picoxystrobin were 1.5–8.6 days in soil and 2.1–2.8 days in peanut seedlings 14 . The dissipation half‐lives of picoxystrobin in oriental melon were 3.4–3.7 days reported by Kabir et al 15 . You et al .…”
Section: Resultsmentioning
confidence: 81%
“…On the whole, pyraclostrobin and picoxystrobin exhibited a rapid dissipation in cucumbers in most sites, which was consistent with literature reports in different matrixs. 14,15,25 For example, Zhu et al reported the half-lives of picoxystrobin were 1.5-8.6 days in soil and 2.1-2.8 days in peanut seedlings. 14 The dissipation half-lives of picoxystrobin in oriental melon were 3.4-3.7 days reported by Kabir et al 15 You et al's results showed pyraclostrobin dissipated quickly in maize plant with half-lives of 1.6 to 1.7 days.…”
Section: Dissipation Behaviors Of Pyraclostrobin and Picoxystrobin Inmentioning
confidence: 99%
See 3 more Smart Citations